Control Interno De Procesos De Recaudacion Y Facturacion De La Gobernacion - Moran Bravo, Maria Gabriela (2018)
The Governors in Ecuador guard the Democratic Stability, Citizen Security and the efficient functioning of the Public institutions present in the Province, whose purpose in our society is to develop and execute the provision of common service to all citizens. The Ministry of the Interior through the Government of Los Ríos, has the mission to develop, proceed and support internal policies aimed at defending public order, security and social peace. The analysis and development of this case study was developed in the GOVERNMENT OF LOS RIOS, which is a non-profit entity, which is focused on the benefit of the citizens of the province of Los Ríos, this institution is located in the city of Babahoyo The purpose of this investigation is to publicize the internal control in the billing and collection processes that are carried out in the financial area of ​​the Department of Collection of the Government of Los Ríos, to know the main activities of the area of ​​collection of the institution. For the realization of this work the descriptive method was used since the description is the product of the observation, a bank of questions was generated addressed to the personnel of the tax collection department, the technique used was the interview which gave us a clear vision of the activities carried out in the collection and billing processes of the Gobernación de los Ríos. This case study is focused on the instructions of the line of research proposed with the School of Accounting and Auditing of the Faculty of Administration, Finance and Informatics of the Babahoyo University. 3 For this reason we have proceeded to guide it to the sub-line of Financial Management and Social Commitment, due to the fact that the administration and compliance of the processes and the responsible personnel involved in said activity are contemplated.